Bram Stoker's Gibbet Hill and Other Lost Writings
XL, 348 p. 43 illus., 7 illus. in color.
Keywords: As Carol A. Senf has noted of some of Bram Stoker’s less prominent ﬁctions in Science and Social Science in Bram Stoker’s Fiction (2002), they often occupy an elusive place, “a realm that is not precisely Gothic but that is somehow beyond the scientiﬁc and rational world of the late nineteenth and early twentieth centuries.” The present anthology demonstrates how even Stoker’s nonfictive works, including his jokes, often find themselves at home in the elusive realm of which Senf is here speaking. After more than six years of archival inquiry, the editors present here nineteen previously unknown or relatively unglimpsed published letters, works of short fiction, and journalistic writing by Stoker (1847-1912), including “Gibbet Hill” (1890), a Gothic short story the editors discovered in 2016. Additionally, they present fifty-five other unknown period writings by or about Stoker, including interviews, public addresses, speeches, and testimonies. The works in this anthology, together with the extensive research offered in the introduction, prefatory note, and annotations, not only highlight the intertextuality between Dracula and other of Stoker’s works, but support the conclusion that Stoker’s periodical writings indeed denote a much greater force in his literary repertoire than previously accepted. Not surprisingly, many of the works in this anthology exhibit the same curious sprinkling of characteristically delicate Gothicisms and “other knowledges” for which Stoker has become known outside of his ubiquitous vampire novel. Paul S. McAlduff is an adjunct professor of English at Jeonnam State University, Damyang, South Korea. He has published in Gothic Studies, ELT: English Literature in Transition, 1880–1920, and the Journal of Dracula Studies. As the managing editor of bramstoker.org, the definitive website dedicated to the works of Bram Stoker, McAlduff has earned international repute as a Stoker bibliographer and archivist. John Edgar Browning, Ph.D., a professor of liberal arts at the Savannah College of Art and Design (SCAD), is an internationally recognized authority on Dracula, Bram Stoker, vampires, and the horror genre. He has written, co-written, or co-edited twenty books and over one hundred shorter works focusing on these topics. In 2021, he co-edited, with David J. Skal, the second Norton Critical Edition of Dracula.